Evaluation of continuous nonaffinity capture chromatography for a recombinant enzyme—optimization for a changing perfusion feedstream and comparison to batch processing. (9th August 2018) - Thompson, Christopher; Wilson, Kelly; Larkin, Christopher; Lee, Jeong; Wang, William K.; Wendeler, Michaela
Abstract : This work presents the optimization and critical evaluation of continuous capture chromatography in the downstream process of a recombinant enzyme. For the upstream manufacturing of this molecule, a perfusion process was implemented due to benefits for product quality and productivity. This process is, however, characterized by low titer and significant changes over the course of the harvest duration in terms of active enzyme concentration and impurity content. We evaluated the feasibility and benefits of a continuous capture operation. This case study illustrates the design approach that can be utilized to address challenges presented by a changing feedstream, and the statistical measures that can be employed to characterize and optimize the operating space under material and time constraints. Process economic modeling in conjunction with Monte Carlo simulations indicate that even for a nonaffinity capture step utilizing a relatively cheap ion‐exchange resin, the smaller column volume used in a continuous set‐up results in cost savings compared to the batch process. We compare this option to the scenario of repeated processing using a small capture column in batch mode. Our analysis establishes that continuous processing becomes economically attractive for processes where only a small portion of the potential column lifetime can be utilized or for column steps with slow mass transport and shallow breakthrough curves. In cases where column breakthrough is sharp and resin lifetime is relatively short, continuous processing may offer an improvement over traditional batch processing, but much of the productivity and cost savings can be realized through repeated column cycling. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 2018 © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:1195–1204, 2018